Experience counts: The role of female age in morning incubation and brooding behavior in relation to temperature. (22nd July 2020) - Williams, Kelly; Sudnick, Madeline; Anderson, Rachel; Fitschen‐Brown, Meredith
Abstract : Reproductive experience can impact how individuals allocate time and energy to reproduction and generate differences in reproductive behavior that leads to experience dependent variation in reproductive success. In order to understand if individual variation in parental behavior is related to environmental temperature and breeding experience, we observed the timing and duration of the first morning off bout in a wild, open cup nesting passerine bird during the incubation and early nestling period. We compared incubation behaviors and nest temperature of inexperienced (second year = first breeding season) and experienced (after second year) female hooded warblers Setophaga citrina . Females left the nest earlier on colder mornings suggesting an energetic constraint due to the long overnight on bout during colder temperatures. During incubation, females increased the duration of the first morning off bout with increasing temperature. Similarly, during the early nestling period, experienced females had shorter off bout duration on colder mornings and increased duration with warmer temperatures. In contrast, inexperienced females increased off bout duration with colder morning temperatures. Experienced females maintained higher nest temperatures and higher minimum nest temperatures compared to inexperienced females. We also found evidence that experienced females nested in microhabitats with higher minimum morning temperature which may buffer older females from colder daily extremes and enable older females to maintain higher nest temperatures. While we found no relationship between incubation and brooding behaviors and fledging success, the proportion of the clutch that hatched was positively related to minimum nest temperature. The ability of experienced females to maintain higher minimum nest temperatures and to adjust brooding behaviors during colder mornings is a potential mechanism that has consequences for nestling condition in a wild population. Our results highlight the need to examine experience‐related parental care behaviors in responding to environmental variation.